Scientific metropolises in the Central Maghreb and their contribution to the revival of the intellectual system in the Middle Ages - gatel, ilhem (The Algerian Historical Journal, 2026)
There is no doubt that the Central Maghreb has inherited an important heritage from the statelets that were established on its soil, starting from the Rustamiya state in Tehert to the Hammadid state in the Citadel and Bejaia, then the Almohad state in Marrakesh, and then the Hafsid state in the eastern part of its soil and the Zayan state in the western part. This accumulated heritage through the scientific movement of the cities of the Central Maghreb contributed to the crystallization of the scientific space of the Central Maghreb during the centuries 7-8-9 AH/13-14-15 CE, which was embodied in the historical astégraphia books that spoke about the Islamic Maghreb as a whole and the Central Maghreb in particular, which were translated She also praised the scientific metropolis of the Central Maghreb and its role in making the learned elites.